Rancang Bangun Sterilisasi Box Menggunakan Sinar-Uv Berbasis Arduino Dan Aplikasi Android Sebagai Sistem Kendali Tanpa Sentuhan - Riri Wulandari Siregar; Abdul Jabbar Lubis; Imran Lubis (Universitas Harapan Medan, 2021)
Around the world, including Indonesia is experiencing attacks of epidemic disease caused by corona virus widely or commonly referred to as a pandemic. It is to be a factor that the public should be more concerned about sterility and hygiene in terms of any kind including objects or goods that are used. Sterilization is a process of killing all forms of life are microorganisms that exist on the objects around the particular environment. One of the steps to pensterilian by utilizing ultraviolet light as a disinfectant to kill the bacteria or virus. Development of boxes of sterilization with the use of UV-rays based on arduino and utilize the android app as a system of control without touch where the device utilizes a of the luminous radiation of ultraviolet rays which have been studied and proven to inhibit the growth of bacteria. Box sterilization using ultraviolet light is able to mensterilisasikan objects before or used without the use of direct touch by hand to clean the objects with the size with a p: 35cm, l:15cm and t:>5cm for 10 minutes.